2012
DOI: 10.1007/s11270-011-1008-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceuticals in Rivers of Two Regions with Contrasted Socio-Economic Conditions: Occurrence, Accumulation, and Comparison for Ukraine and France

Abstract: International audienceThe goal of our study was to identify pharmaceuticals, their potential sources and consumption level in two different socioeconomic and geographical regions--Bordeaux, France and Kharkiv, Ukraine. These substances were monitored in rivers water during contrasted seasonal conditions with application of passive samplers. The 21 pharmaceuticals (psychiatric drugs: alprazolam, amitriptyline, diazepam, fluoxetine, nordiazepam, carbamazepine, bromazepam; analgesics: aspirin, paracetamol; bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(25 citation statements)
references
References 42 publications
0
22
0
2
Order By: Relevance
“…Several monitoring studies have reported the presence of pharmaceuticals in urban wastewaters (Al-Rifai et al, 2007;Brown et al, 2006;Bueno et al, 2012;Gracia-Lor et al, 2011;Gros et al, 2006;Pedrouzo et al, 2011) and surface waters (Daneshvar et al, 2010;González Alonso et al, 2010;Kolpin et al, 2002;Martín et al, 2011;Spongberg et al, 2011;Vystavna et al, 2012). Nevertheless, few data is available on the contribution of hospital effluents towards the load of pharmaceuticals in WWTPs (Beier et al, 2011;Langford and Thomas, 2009;Ort et al, 2010;Thomas et al, 2007;Verlicchi et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Several monitoring studies have reported the presence of pharmaceuticals in urban wastewaters (Al-Rifai et al, 2007;Brown et al, 2006;Bueno et al, 2012;Gracia-Lor et al, 2011;Gros et al, 2006;Pedrouzo et al, 2011) and surface waters (Daneshvar et al, 2010;González Alonso et al, 2010;Kolpin et al, 2002;Martín et al, 2011;Spongberg et al, 2011;Vystavna et al, 2012). Nevertheless, few data is available on the contribution of hospital effluents towards the load of pharmaceuticals in WWTPs (Beier et al, 2011;Langford and Thomas, 2009;Ort et al, 2010;Thomas et al, 2007;Verlicchi et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…In US and Europe, more than 80 PPCPs were detected at concentrations of up to mg/L level in different water bodies [78,83,84]. Based on the research carried out by Vystvna et al [85], it was suggested that diclofenac, caffeine and carbamazepine are useful chemical markers for tracing wastewater contamination in France and Ukraine. Similarly, the use of persistent marker (carbamazepine) and labile markers (acetaminophen and salicylic acid) has been successfully applied to detect wastewater contamination in surface water and groundwaters by Tran et al [29].…”
Section: Pharmaceuticals and Personal Care Products (Ppcps)mentioning
confidence: 99%
“…Screening studies usually cover a wide range of chemicals in order to monitor local contamination and/or its seasonal changes. Vystavna et al (2012; even compare the profiles obtained from two different regions with contrasting socio-economic conditions. In some cases, only a specific range of substances is included in the study.…”
Section: Target Analytes and Sampling Sitesmentioning
confidence: 99%
“…Other extraction media, e.g. ACN (Amdany et al 2014a), acetone (Tanwar et al 2015), MeOH/water (Bailly et al 2013;Creusot et al 2014) or MeOH/dichloromethane (Vystavna et al 2012;Creusot et al 2013;Morin et al 2013;Vystavna et al 2013) are also suitable. Some authors adjust the pH in order to improve the extraction (Harman et al 2011;Cernoch et al 2012;Bayen et al 2014;Shi et al 2014).…”
Section: Extraction and Analytical Techniquesmentioning
confidence: 99%